Ecological And Pathological Studies Of Gill Monogeneans In Floating Cage Cultured Seabass Lates Calcarifer (Bloch) - Balasuriya, L.K.S.W. (1994)
Gill monogeneans were observed to be the most serious parasitic disease problem in floating cage cultured seabass in Malaysia. It appeared that they were the primary cause for bacterial infections. which often caused severe mortalities. Three species of diplectanid monogeneans. Pseudorhabdosynochus Latesi (Tripathi 1955). P. monosquamodiscusi (Balasuriya and Leong 1994) and DipLectanwn penangi (Liang and Leong 1991) occurred on the gills. the former two often with a high prevalence and mean intensity.